OPTIMIZATION OF A CRUDE DISTILLATION UNIT USING PARAMETRIC DESIGN OF TAGUCHI AND RESPONSE SURFACE METHODS - ALI, SYED FAIZAN (2014)
This research work proposes a systematic procedure for determining and reducing the number of decision variables in the case of operational optimization of a crude distillation unit (CDU). The proposed procedure is based on the parametric design of the Taguchi and response surface methods. The Taguchi method quantifies the significance of variables based on their contribution factors. Variables with more than 90% contribution factors are selected and validated with the response surface method. A sequential quadratic programming (SQP) algorithm is then employed to optimize a profit function based onthereduced number of decision variables.